Laboratory investigation and core flood demonstration of enhanced biogenic methane generation from lignite - Basera, Priyanka; Lavania, Meeta; Singh, Nimmi; Lal, Banwari (Frontiers in Bioengineering and Biotechnology, 2024)
Over the last several decades, coalbed methane (CBM) has emerged as an important energy source in developing nations like India as well as worldwide and is expected to play a significant role in the energy portfolio of the future.The current scenario of rapid exhaustion of fossil fuels is leading to the need to explore alternative and efficient fuel resources. The present study demonstrates enhanced methane production per gram of lignite (lowest-rank coal).Optimization of the bioconversion of lignite to methane revealed 55 °C temperature and 1.5 g/l NaCl concentration as ambient conditions for the process. A scale-up study in the optimized condition showed 2800 mM methane production per 25 g of lignite in anaerobic conditions.Further, Fourier transform Infrared (FTIR) and Gas Chromatography Mass Spectrometry (GCMS) analysis showed bioconversion of lignite into simpler intermediate substrates required for methane production. The results highlighted that the bacterial bacterial action first converts lignite into volatile fatty acids, which subsequently get converted into methane . Further, the exploration of indigenous microbial consortia in Tharad well (THAA) mainly comprises the order Methanosarcinales and Methanomicrobiales. The pathogenicity of the microbial consortium THAA was declared safe for use in mice via the oral route by The Energy and Resources Institute (TERI), India . The study demonstrated the development of indigenous consortia (TERI THAA), which can potentially enhance methane production from the lowest coal grade under extreme conditions in Indian coal beds.